Threshold Results for Semilinear Parabolic Equations with Nonlinear Boundary Conditions (Journal of Partial Differential Equations, 1995)
This paper deals with the following semilinear parabolic equations with nonlinear boundary conditions u_t - Δu = f(u) - λu,x ∈ Ω, t > 0 \frac{∂u}{∂n} = g(u), \qquad x ∈ ∂Ω, t > 0 It is proved that every positive equilibrium solution is a threshold.